King Lear and King Solomon - Seferyan, Sona (Armenian Folia Anglistika, 2007)
The article draws parallels between Solomon the Wise and King Lear who has suffered a lot and has acquired wisdom. Shakespeare wrote his tragedy as a servant to King James I. He was inspired by the love and admiration his king, who was regarded the wisest fool of the Christian world, held for Solomon the Wise.